A Self-Assessment and Peer Feedback Tool for Leader Development - Barry, Erin S.; McManigle, John E.; McManigle , John E. (Journal of Leadership, Accountability and Ethics, 2023)
Self-awareness is essential to leader development. Internal self-awareness refers to how well we see and understand ourselves and our impact on others. External self-awareness refers to the extent to which we understand how others see us. To optimize self-awareness, it is important to receive and provide frank and meaningful feedback. These skills can improve leader performance, increase self-awareness, and enhance development. Currently, there are few instruments that provide information about self-awareness. The creation of a self-assessment and peer feedback tool would help provide individuals with clear assessments of their leadership knowledge and skills as well as perspectives from peers with whom they work closely. This article describes the development of a self-assessment and peer feedback tool based on a LeaderFollower Framework. This tool can be used within leader development programs to enhance selfawareness and peer perceptions to further develop leaders.